Dynamic Viscosity of Gases at Temperature and Pressure - Hajibalayev, E.R. (Herald of Azerbaijan Engineering Academy, 2023)
The following issues are considered in the article: the concept of viscosity in liquids and gases; the effect of pressure and temperature changes on the process. Dependence of viscosity of natural gas on pressure and temperature. Based on laboratory studies, the analysis was performed using the small squares method and an empirical equation was obtained. Determining the error in a given value of the correlation coefficient.